Comprehensive geriatric assessment in the emergency department: A protocol for a prospective cohort study [version 2; peer review: 2 approved] - Colin Quinn; Ali Sheikhi; Elaine Shanahan; Aoife Leahy; Katie Robinson; Damien Ryan; Denys Shchetkovsky; Margaret O'Connor; Mairéad Conneely; Rose Galvin; Íde O'Shaughnessy; Leonora Carey; et al. (HRB Open Research, 2022)
Background: Comprehensive geriatric assessment (CGA) has been shown to improve outcomes in hospitalised older adults; however, there is currently no compelling evidence to support CGA interventions within the Emergency Department (ED). The aim of this study is  to explore the clinical and process outcomes of older adults who receive ED-CGA over a period of six months after their initial ED attendance. Design: Prospective cohort study. Methods: The STrengthening the Reporting of the OBservational studies in Epidemiology (STROBE) standardised reporting guidelines will be adhered to. Older adults aged ≥65 years who score ≥2 on the Identification of Seniors at Risk (ISAR) tool and present to the ED with a medical complaint during the operational hours of the dedicated interdisciplinary team, will be considered eligible for recruitment. Demographic and health assessment information will be obtained at the ED index attendance followed by completion of an interdisciplinary CGA. A dedicated research nurse will complete follow-up telephone interviews with participants at 30 days and six months. The primary outcome will be incidence of hospital admission from the ED index attendance. Secondary outcomes will include functional decline, patient satisfaction with the ED index attendance, unscheduled ED reattendance(s), unscheduled hospital (re)admission(s), nursing home admission(s), healthcare utilisation, and death. Descriptive statistics will be used to profile the characteristics of the study participants and multivariate logistic and linear regression analysis will be used to analyse risk of adverse outcomes. Ethics and dissemination: Ethical approval was granted by the University of Limerick Hospital Group Research Ethics Committee (107/2021). The authors will disseminate study findings through publication in a peer-reviewed journal and presentation at national and international conferences. Patient and public involvement will be sought from a panel of older adults at the Ageing Research Centre in the University of Limerick. Clinicaltrials.gov Identifier: NCT05252182.